Efficacy analysis of splint combined with platelet-rich plasma in the treatment of temporomandibular joint osteoarthritis - Wu, Chuan-Bin; Sun, Ning-Ning; Zhang, Dan; Wang, Qiang; Zhou, Qing (Frontiers in Pharmacology, 2022)
Objective: To evaluate the efficacy of splints combined with PRP for the treatment of temporomandibular joint osteoarthritis. Methods: Thirty-one patients with temporomandibular joint osteoarthritis who were treated with splints combined with platelet-rich plasma (PRP) from January 2021 to June 2021 at the Department of Oral and Maxillofacial Surgery, School of Stomatology, China Medical University (Shenyang, China) were retrospectively reviewed. The VAS scores of all the patients were recorded before and 6 months after treatment, and the maximum comfortable mouth opening was recorded. All data were analyzed by the paired t-test using SPSS software, and a p-value < 0.05 indicated statistically significant differences. Results: Splint + PRP treatment was successful in 31 patients. The mean pretreatment VAS score was 6.1, and the mean VAS score 6 months posttreatment was 4.1. The posttreatment VAS score was significantly lower than the preoperative VAS score (p < 0.05). The mean pretreatment maximum comfortable mouth opening (MCMO) was 27.6 mm, and the mean MCMO 6 months posttreatment was 34.8 mm. The MCMO was significantly increased (p < 0.05). Conclusion: Splint + PRP is an effective treatment for temporomandibular joint osteoarthritis.